Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Multiply (x+2)(x+3)(x-1)?

I'm sure its really easy, but I am just not getting it right now. Does it equal X^3+4x^2+x-6?

4 Answers

Relevance
  • Anonymous
    9 years ago
    Favorite Answer

    (x+2)(x+3)(x-1)

    =(x^2+2x+3x+6)(x-1)

    =(x^2+5x+6)(x-1)

    =(x^3+5x^2+6x-x^2-5x-6)

    =x^3+4x^2+x-6

    So yes you are right

    I hope that helps!

  • 9 years ago

    Yes its true.

    Your question:

    (x+2)(x+3)(x-1)

    First, multiply the first two parenthesis:

    = (x^2+3x+2x+6)(x-1)

    = (x^2+5x+6)(x-1)

    Then solve for the third parenthesis:

    = (x^3-x^2+5x^2-5x+6x-6)

    = (x^3-4x^2+x-6)

    Source(s): My own Math knowledge.
  • Kuyuk
    Lv 4
    9 years ago

    (x+2)(x+3)(x-1)?

    (x+2)(x+3)= x^2 +5x +6 (x-1) =

    x^3 +4x^2 +x -6

  • 9 years ago

    x^3+4x^2-x-6

Still have questions? Get your answers by asking now.